Pengaruh Video Animasi Tentang Hak Dan Kewajiban Terhadap Tingkat Pemahaman Pasien Di Puskesmas Pandanwangi Kota Malang - Eiska Rohmania Zein; Fayza Firdaus Tsania (Kementerian Kesehatan Poltekkes Malang, 2024)
Patient rights and obligations are important things that patients need to know to ensure a smooth patient service process at the Puskesmas. The aim of this research is to determine the level of patient understanding between before and after the implementation of the animated video about rights and obligations at the Pandanwangi Health Center, Malang City. This research method uses analytical quantitative research methods. The sample in this study was 33 outpatients at the Pandaan Community Health Center. The research was conducted in January-February 2023. Patients were given an animated video regarding information on their rights and obligations at the Pandanwangi Community Health Center. Increased knowledge was measured using a questionnaire before and after watching the video. The data analysis technique in this research is the Paired Sample T Test statistical test technique which is used to determine the difference in the patient's level of understanding before and after being given the animated video. The results of statistical tests show that there is a difference in the average value of patient understanding between before and after being given an animated video about the rights and obligations of patients at the Pandanwangi Community Health Center, Malang City.